INFLUENCE OF PERCEIVED EASE, USEFULNESS, AND BEHAVIORAL CONTROL ON STUDENTS’ SHARIA INVESTMENT INTEREST IN YOGYAKARTA - Yuni Purnawati; Mahendra Adhi Nugroho (Universitas Airlangga, 2026)
This study aims to examine the influence of Perceived Ease of Use, Perceived Usefulness, and Behavioral Control on students’ interest in Sharia investment through online investment platforms in the Special Region of Yogyakarta (DIY). This research employs a quantitative approach with a sample of 416 student respondents who have engaged in investment activities and used online investment platforms. Data were collected using a Likert-scale-based questionnaire. Data were analyzed using Structural Equation Modeling with a Partial Least Squares (SEM-PLS) approach. The analyses conducted include the assessment of the Outer Model, Inner Model, and Bootstrapping. Thefindings indicate that Perceived Ease of Use of online investment platforms and Behavioral Control have a positive and significant effect on students’ interest in Sharia investment in DIY. Meanwhile, Perceived Usefulness does not have a significant effect on students’ interest in Sharia investment in DIY.